GLP-1 Receptor Antagonists in Heart Failure with Reduced and Preserved Ejection Fraction: A Scoping Review of Pathogenesis, Efficacy and Future Directions - Imran, Fajr; Hussain, Mubashir; Mushtaq, Usman; Khaliq, Izza; Masood, Shahid; Zafar, Qasim (Indus Journal of Bioscience Research, 2025)
Heart failure (HF) still stands as a significant source of morbidity and mortality globally; HFrEF and HFpEF are separate disease processes that require optimal management strategies. There is growing information pointing towards the fact that the GLP-1 receptor has a significant role in cardiovascular biomechanics. Although cardiovascular benefits have been reported in regard to GLP-1 receptor agonists, fewer studies have focused on the effects of GLP-1 receptor antagonists in HF. The objective of this scoping review is to synthesize the current literature regarding GLP-1 receptor antagonists particularly in HF with regards to their pathophysiological effects, clinical outcomes, and possible future roles. An extensive bibliographic search employing MEDLINE, EMBASE, CINAHL, Web of Science, and Scopus databases were conducted according to the PRISMA-ScR statement. Thus, 12 articles were used for the synthesis of the study, including both preclinical research trials and clinical. The results show that GLP-1 receptor antagonism must be avoided given the detrimental effects which it has on cardiac function such as reduced myocardial glucose utilization, stormed neurohormonal axis activity, and elevated systemic inflammation. However, the general benefits have prompted more intense further research at the same time, whether there are benefits for particular subgroups. More research is required, including multicenter, large-scale RCTs, to determine the applicability of GLP-1 receptor antagonists in HF. Learning about their functioning and potential applications could shed light on new approaches for treating this condition.